Multidisciplinary Healthcare Team In The Management Of Colon Diverticulitis: Nursing, Radiology, Pharmacy, And Laboratory Perspectives (The Review of Diabetic Studies, 2024)
Background: Diverticulitis has become increasingly prevalent, especially in Western countries, contributing significantly to healthcare utilization and cost. Although traditionally associated with older adults, recent evidence shows rising incidence among younger populations. The condition ranges from uncomplicated inflammation to severe complications such as abscess, perforation, fistula, or peritonitis.Aim: This article aims to present a comprehensive overview of diverticulitis from a multidisciplinary healthcare perspective, highlighting contributions from nursing, radiology, pharmacy, and laboratory services in diagnosis, management, and patient outcomes.Methods: A narrative clinical review was developed using current epidemiological data, pathophysiological insights, diagnostic strategies, and evidence‑based management guidelines. The experiences and roles of multidisciplinary teams were integrated to illustrate collaborative care pathways.Results: Findings emphasize the multifactorial nature of diverticulitis, influenced by genetic, environmental, dietary, and lifestyle factors. CT imaging emerged as the diagnostic gold standard due to high sensitivity and specificity. Most uncomplicated cases respond to conservative outpatient therapy, while complicated disease warrants hospitalization and, in some cases, surgical intervention. Multidisciplinary collaboration significantly improves diagnostic accuracy, optimizes treatment decisions, enhances patient education, and reduces recurrence risk. Evidence also highlights evolving trends, including selective use of antibiotics and individualized decisions for elective colectomy.Conclusion: Effective diverticulitis management requires integrated efforts across clinical disciplines. Early diagnosis, risk‑based treatment selection, lifestyle modification, and coordinated follow‑up are essential to improving outcomes and reducing recurrence.